Aggregation-induced emission (AIE)-Based nanocomposites for intracellular biological process monitoring and photodynamic therapy. (August 2022) - Lin, Xiangfang; Li, Wei; Wen, Yongqiang; Su, Lei; Zhang, Xueji
Abstract: As a non-invasive visualization technique, photoluminescence imaging (PLI) has found its huge value in many biological applications associated with intracellular process monitoring and early and accurate diagnosis of diseases. PLI can also be combined with therapeutics to build imaging-guided theragnostic platforms for achieving early and precise treatment of diseases. Photodynamic therapy (PDT) as a quintessential phototheranostics technology has gained great benefits from the combination with PLI. Recently, aggregation-induced emission (AIE)-active materials have emerged as one of the most promising bioimaging and phototheranostic agents. Most of AIEgens, however, need to be chemically engineered to form versatile nanocomposites with improved their photophysical property, photochemical activity, biocompatibility, etc. In this review, we focus on three categories of AIE-active nanocomposites and highlight their application progresses in the intracellular biological process monitoring and PLI-guided PDT. We hope this review can guide further development of AIE-active nanocomposites and promote their practical applications for monitoring intracellular biological processes and imaging-guided PDT.